2008
DOI: 10.1097/pas.0b013e318150d51b
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplastic/Serrated Polyposis in Inflammatory Bowel Disease

Abstract: Herein, we describe the clinical, pathologic, immunohistochemical, and molecular features of 3 unique patients with long standing inflammatory bowel disease, all of whom developed numerous discrete hyperplastic/serrated colonic polyps similar to those described in the hyperplastic/serrated polyposis syndrome. The 3 patients (2 with ulcerative colitis and 1 with Crohn ileo-colitis) were evaluated for a variety of clinical, histologic (including the type, location and number of polyps in the colon), and immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Kilgore et al 15 reported non-dysplastic serrated lesions in 33% of cancer-bearing resection specimens from patients with Crohn's disease compared with 10% of controls without cancer. Srivastava et al 17 described patients with longstanding inflammatory bowel disease and multiple hyperplastic polyps and sessile serrated adenoma/polyps (reminiscent of the serrated polyposis syndrome), nearly half of which contained KRAS but not BRAF mutations. They reported that cancers developed in two patients with conventional adenomatous dysplasia or traditional serrated adenomas but not in a third patient with non-dysplastic serrated lesions.…”
Section: Modern Pathology (2015) 28 1584-1593mentioning
confidence: 99%
See 1 more Smart Citation
“…Kilgore et al 15 reported non-dysplastic serrated lesions in 33% of cancer-bearing resection specimens from patients with Crohn's disease compared with 10% of controls without cancer. Srivastava et al 17 described patients with longstanding inflammatory bowel disease and multiple hyperplastic polyps and sessile serrated adenoma/polyps (reminiscent of the serrated polyposis syndrome), nearly half of which contained KRAS but not BRAF mutations. They reported that cancers developed in two patients with conventional adenomatous dysplasia or traditional serrated adenomas but not in a third patient with non-dysplastic serrated lesions.…”
Section: Modern Pathology (2015) 28 1584-1593mentioning
confidence: 99%
“…9,[11][12][13] Nonetheless, recognition of the full range of histologic lesions with malignant potential in the setting of inflammatory bowel disease is incomplete. Although several prior studies have described serrated colorectal lesions in patients with inflammatory bowel disease, [14][15][16][17] a systematic characterization of serrated polyps in this population has not been hitherto reported. We hypothesized that serrated polyps in patients with inflammatory bowel disease may have similar biologic characteristics to sporadic serrated polyps and therefore undertook a retrospective review of colorectal serrated polyps diagnosed over a 14-year period among inflammatory bowel disease patients undergoing routine colonoscopic surveillance at our institution.…”
mentioning
confidence: 99%
“…Thus, current screening algorithms may not be adequate for detection. Moreover, hyperplastic/ serrated polyposis has also been observed in patients with chronic inflammatory bowel disease [14] . A prudent approach has been suggested to include complete resection and surveillance examinations as often as the intervals defined for the more traditional adenomatous polyps but this approach is not necessarily reflective of the natural biological history of these lesions.…”
Section: Future Screening For Colon Polypsmentioning
confidence: 99%
“…Serrated lesions may be associated with neoplastic progression in IBD; some have been reported to be associated with invasive adenocarcinoma. 110 However, data are limited and further investigation is needed for characterization. 95,[110][111][112] Patients with sessile serrated polyp-like lesions in the diseased colon should have repeat colonoscopy in 1 year following complete removal of the lesion (W. E. Jackson et al, unpublished data, 2015).…”
Section: Unconventional Precursor Lesionsmentioning
confidence: 99%
“…110 However, data are limited and further investigation is needed for characterization. 95,[110][111][112] Patients with sessile serrated polyp-like lesions in the diseased colon should have repeat colonoscopy in 1 year following complete removal of the lesion (W. E. Jackson et al, unpublished data, 2015). In addition, villous hypermucinous mucosa harboring K-RAS mutation and very well-differentiated adenocarcinoma with low-grade dysplastic precursor lesions have been described in IBD.…”
Section: Unconventional Precursor Lesionsmentioning
confidence: 99%